Exploring research dynamics of PDT in anti-infective applications (2004–2024): a bibliometric perspective - Wen, Wen; Liang, Shuang; Zhang, Yun; Lin, Meiyuan; Gao, Yuan; Deng, Jun (Frontiers in Pharmacology, 2025)
BackgroundPhotodynamic therapy (PDT) has become a popular research direction in the field of infection control; however, there is still a lack of systematic bibliometric analysis. This paper aims to fill this gap by conducting the first comprehensive bibliometric analysis of studies related to PDT in infection control over the past 20 years, in order to gain in-depth insights into its current status and emerging trends.MethodsPublications related to PDT and infection control were collected from the Web of Science Core Collection database (WoSCC) from January 2004 to April 2024. Microsoft Excel was used to organize the data and analyze annual publication trends, while VOSviewer and CiteSpace were employed for the visual analysis of the selected literature.ResultsA total of 9,711 articles and reviews meeting the inclusion criteria were retrieved for this study. Over the past two decades, publications in the field of PDT for infection control have exhibited a marked upward trajectory. China leads globally in research output and influence within this domain, establishing robust collaborative networks with the United States and Brazil. The most productive institution, journal, and author were the Universidade de São Paulo, Photodiagnosis and Photodynamic Therapy, and Michael R. Hamblin, respectively. Early studies frequently featured keywords such as “5-aminolevulinic acid,” “photosensitization,” “toluidine blue O,” and “photodynamic inactivation.” In contrast, recent research has shifted toward innovative themes such as “nanoparticles,” “antibacterial nanomaterials,” “aggregation-induced emission,” and “photothermal therapy.” Nanotechnology-based synergistic enhancement strategies for PDT and antimicrobial photodynamic therapy (aPDT) represent a current research hotspot. Nine emerging themes — “aggregation-induced emission,” “wound healing,” “photothermal therapy,” “sonodynamic therapy,” “antioxidant,” “formulation,” “design,” “nanosheets,” and “graphene oxide”—have notably influenced future directions and warrant special attention.ConclusionThis study is the first to comprehensively summarize the research trends and progress in PDT for anti-infective treatment through bibliometric analysis, and to clarify recent research frontiers and hot directions, providing a valuable reference for the continued exploration of PDT applications in anti-infective therapy.